Pengaruh Kemampuan Kerja, Motivasi Kerja dan Komitmen Organisasi Terhadap Kinerja Pegawai Badan Pendapatan Daerah Kab. Malang pada Bidang PBB P2 - Soerya Mahatma Wisnoe; Hadi Sunaryo; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis reseacrh purpose to determine: 1) Description of ability work, motivation work, organizational commite and the ability Badan Pendapatan Daerah Kabupaten Malang mojor of PBB-P2. 2) The effect of ability work, motivation work, organizational commite and the ability Badan Pendapatan Daerah Kabupaten Malang mojor of PBB-P2. 3) The effect of potentiality work support to employee work competence at Badan Pendapatan Daerah Kabupaten Malang mojor of PBB-P2. 4) The effect of motivation work support to employee work competence at Badan Pendapatan Daerah Kabupaten Malang mojor of PBB-P2. 5) The Effect of organization commite support to employee work competence at Badan Pendapatan Daerah Kabupaten Malang mojor of PBB-P2.The Method used in this research is quantitative with descriptive approach and conducted at Badan Pendapatan Daerah Kabupaten Malang mojor of PBB-P2 with total pupulation 42 employees. Data collection technique used questionnaire with likert scale measurement. The result of this research indicate that: 1) Ability work, Motivation work and organization commite does a significant effect to employee work competencee at Badan Pendapatan Daerah Kabupaten Malang mojor of PBB-P2. 2) The ability work does a significant effect to employee work competencee at Badan Pendapatan Daerah Kabupaten Malang mojor of PBB-P2. 3) The Motivation work does a significant effect to employee work competencee at Badan Pendapatan Daerah Kabupaten Malang mojor of PBB-P2. 4) The Organization Commite does a significant effect to employee work competencee at Badan Pendapatan Daerah Kabupaten Malang mojor of PBB-P2.Keywords: employee work competencee, ability work, motivation work, organization commite